A First Course in Aerial Robots and Drones - Bestaoui Sebbane, Yasmina (Boca Raton, FL : CRC Press, 2022)
"A First Course in Aerial Robots and Drones provides an accessible and student friendly introduction to aerial robots and drones. Drones figure prominently as opportunities for students to learn various aspects of aerospace engineering and design. Drones offer an enticing entry point for STEM studies. As the use of drones in STEM studies grows, there is an emerging generation of drone pilots who are not just good at flying, but experts in specific niches, such as mapping or thermography. Suitable for undergraduate students, this textbook provides students and other readers with methods for solving problems and improving their science skills"--
Includes bibliographical references and index.
Keywords: Drone aircraft -- Textbooks; Airplanes -- Radio control -- Textbooks